49.1k views
5 votes
Solve the equation for x:
-3(x + 4) + 5x = 24

User Galakt
by
5.8k points

2 Answers

2 votes

Answer:


-3(x + 4) + 5x = 24\\\\-3x - 12 + 5x = 24\\\\2x - 12 = 24\\\\2x = 36\\\\x = 18

The solution for x in this equation is 18.

User Suho
by
5.2k points
5 votes

Answer:

x = 18

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

Explanation:

Step 1: Define

-3(x + 4) + 5x = 24

Step 2: Solve for x

  1. Distribute -3: -3x - 12 + 5x = 24
  2. Combine like terms: 2x - 12 = 24
  3. Isolate x term: 2x = 36
  4. Isolate x: x = 18

Step 3: Check

Plug in x into the original equation to verify it's a solution.

  1. Substitute in x: -3(18 + 4) + 5(18) = 24
  2. Add: -3(22) + 5(18) = 24
  3. Multiply: -66 + 90 = 24
  4. Add: 24 = 24

Here we see that 24 does indeed equal 24.

∴ x = 18 is the solution to the equation.

User Docmurloc
by
5.8k points